Do we need a new Fleming époque: The nightmare of drug-resistant tuberculosis - Giovanni Sotgiu; Rosella Centis; Lia D'Ambrosio; Marina Tadolini; Paolo Castiglia; Giovanni Battista Migliori (International Journal of Mycobacteriology, 2013)
Tuberculosis represents an important clinical and public health problem globally, particularly in low- and middle-income countries. During the last 20 years, two relevant events has changed the epidemiology of the disease: the spread of the TB/HIV co-infection and the emergence and spread of the multi-drug resistance tuberculosis (i.e., tuberculosis caused by strains resistant to at least isoniazid and rifampicin). The latter phenomenon has been generated by the inappropriate management of the anti-tuberculosis drugs. Currently, the World Health Organization estimates at least 600,000 MDR-TB cases worldwide, particularly in China, India, South Africa, and in former Soviet Union countries. Unfortunately, new difficult-to-treat MDR-TB cases have been described, named XDR- or TDR-TB (extensively or totally drug-resistant tuberculosis, respectively). Numerous observational retrospective studies proved the poorer prognostic profile of the MDR-TB cases when compared with drug-susceptible tuberculosis. The clinical management of the patients with an XDR and beyond pattern is complicated owing to the poorest, expensive, and toxic therapeutic options. MDR-TB is currently under-reported because of methodological issues, mainly related to the poor proficiency of laboratory testing. National public health strategies should reduce the increase of tuberculosis cases without therapeutic alternatives. Furthermore, research and development activities, based on continuous and sustained funding, should be improved, together with the implementation and the scale-up of effective infection control measures in healthcare settings and in the community.